Dupilumab as a treatment for a case of benign familial pemphigus - Machynia, Kyle T. (International Journal of Research in Dermatology, 2024)
Hailey-Hailey disease (HHD) is an uncommon autosomal dominant genodermatosis characterized by recurrent blistering eruptions primarily affecting intertriginous areas, leading to the formation of eroded, erythematous plaques within flexural skin folds. The condition significantly impairs quality of life due to the frequency of infections, exacerbated by the limited and often ineffective therapeutic options currently available for HHD. In this report, we present a compelling case of HHD successfully treated with dupilumab, highlighting remarkable improvement observed within just two weeks of initiating treatment with this novel therapeutic agent. This promising outcome underscores the potential of dupilumab in managing challenging cases of HHD and warrants further exploration in larger clinical trials.